Cardiac Mapping 2012
DOI: 10.1002/9781118481585.ch14
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Atrial Fibrillation

Abstract: Computer modeling of atrial fibrillation (AF) is considered today as a potentially effective tool for better understanding AF mechanisms and for the development of therapeutic options. Computer models are based on an integrative approach, from the molecule to the patient, incorporating data about cell electrophysiology, cell-to-cell coupling and atrial anatomy. The link to clinical experiments is provided by the computation of endocardial electrograms or surface electrocardiograms (ECG). In this chapter we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The computer modeling approach is currently the only way to compare a variety of ablation strategies on the same heart and can be used for ablation planning and guidance . Earlier computer modeling studies were utilized to test the effectiveness of different PV isolation ablation patterns and to evaluate ablation lesion gaps . A recent study identified optimal ablation targets with smallest amount of tissue ablated to terminate left atrial flutter using patient‐specific models based on in vivo late gadolinium–enhanced MRI …”
Section: Discussionmentioning
confidence: 99%
“…The computer modeling approach is currently the only way to compare a variety of ablation strategies on the same heart and can be used for ablation planning and guidance . Earlier computer modeling studies were utilized to test the effectiveness of different PV isolation ablation patterns and to evaluate ablation lesion gaps . A recent study identified optimal ablation targets with smallest amount of tissue ablated to terminate left atrial flutter using patient‐specific models based on in vivo late gadolinium–enhanced MRI …”
Section: Discussionmentioning
confidence: 99%
“…Activation time was 132 ms. The activation pattern has been previously compared to clinical data and other computer models [10,2]. After left-right conduction delay was introduced (Fig.…”
Section: Simulated Atrial Activitymentioning
confidence: 99%
“…1A). The geometry was derived from an imaging dataset of a patient with AF [10] and included the atria, atrial and ventricular blood cavities, the lungs and the torso. The atrial model (Fig.…”
Section: Simulationsmentioning
confidence: 99%
“…Generic computer models of atrial electrical activation provide a powerful framework for understanding the structure-function basis of reentrant atrial arrhythmias. This view has motivated numerous recent models of atrial electrical function [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], especially since Harrild and Henriquez published the first 3D electrical conduction in a realistic human bi-atrial geometry in 2000 [ 21 ]. Harrild and Henriquez’s computer model incorporates both the left and right atrial chambers and major muscle bundles, including the crista terminalis (CT), pectinate muscles (PMs) and Bachmann’s bundle (BB).…”
Section: Generic 3d Computer Modelsmentioning
confidence: 99%
“…However, whether to isolate individual PV exclusively or together, with or without additional ablation strategies, such as the linear ablation approach, is still an ongoing debate [ 7 ]. Kappenberger et al have developed and studied different ablation patterns systematically using a simplified atrial geometric model of chronic AF in the past decade [ 20 , 35 , 36 , 37 , 39 , 40 ]. In their studies, a monolayer model instead of a structurally-detailed model was constructed based on the endocardial contour of the clinical MRI of human atria to alleviate the computational load.…”
Section: Modeling Pulmonary Vein (Pv) Isolations Using Clinically-mentioning
confidence: 99%